Sleep Disturbances and Suicidality in Posttraumatic Stress Disorder: An Overview of the Literature - Weber, Franziska C.; Norra, Christine; Wetter, Thomas C. (Frontiers in Psychiatry, 2020)
A causal relationship between sleep disturbances and suicidal behavior has been previously reported. Insomnia and nightmares are considered as hallmarks of posttraumatic stress disorder (PTSD). In addition, patients with PTSD have an increased risk for suicidality. The present article gives an overview about the existing literature on the relationship between sleep disturbances and suicidality in the context of PTSD. It aims to demonstrate that diagnosing and treating sleep problems as still underestimated target symptoms may provide preventive strategies with respect to suicidality. However, heterogeneous study designs, different samples and diverse outcome parameters hinder a direct comparison of studies and a causal relationship cannot be shown. More research is necessary to clarify this complex relationship and to tackle the value of treatment of sleep disturbances for suicide prevention in PTSD.